ANALISIS TENTANG PENGGUNAAN MEDIA PEMBELAJARAN PADA MATA PELAJARAN EKONOMI MATERI AKUNTANSI KELAS XI IPS DI SMA NEGERI 22 SURABAYA - NURUL KURNIAWATI (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2013)
Instructional media is use to gain the aims in teaching learning process. This study aimed to describe the materials used, the reasons teachers use instructional materials and to investigate the feasibility of teaching materials used in XI IPS Class at SMA Negeri 22 Surabaya. This study is kind of descriptive study with quantitative approach. Techniques of data collection are documentation, interviews and expert review of the media. Technique of data analysis is descriptive analysis and to measure the feasibility of the media instructional is descriptive quantitative. The result of this study shows that powerpoint is the most usually media being used by the teacher. Beside that, based of the media expert reviewer shows that powerpoint which is used in first Base Competence to fifth BaseCompetence in XI IPS class of SMA Negeri 22 Surabaya is feasible. Keywords:media, accounting, SMA